Detección de mosquitos Anopheles infectados naturalmente con Plasmodium spp. en Puerto Libertador, Córdoba, Colombia (2011)
ABSTRACT: Anopheles species vary in their ability to transmit malaria parasites; therefore, it is important to conduct studies directed to determine the species present in malaria endemic regions and establish their role in transmission. Objective To determine the Anopheles species involved in malaria transmission in the locality of Juan José, Puerto Libertador, Cordoba, Colombia. Materials and methods Natural infectivity by Plasmodium vivax VK210, P. vivax VK247 and Plasmodium falciparum was evaluated by ELISA using pools of the head and thorax of five mosquitoes of the same species per well. ELISA results with values greater than the cutoff point were confirmed by a second ELISA and nested PCR. Results From 2,054 specimens evaluated by ELISA, 2,038 were Anopheles (Nyssorhynchus) nuneztovari Gabaldon; from these, three specimens were found infected, two with P. vivax VK210 and one with P. falciparum, representing an infection rate of 0.15%. Of 16 An. (Nys.) darlingi Root evaluated, none was found infected. Conclusions An. nuneztovari and An. darlingi, two main malaria vectors of Colombia were present in Juan Jose, Puerto Libertador; however, only An. nuneztovari was found infected, indicating its role in transmission in this locality. Further sampling in Juan Jose will allow for a better understanding of the role of An. darlingi in transmission. This information will contribute to the design and implementation of targeted and effective control measures.